(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article provides an insight into the origins of primitive religious prohibitions (taboos)and their role in society. In theology, the concept of taboo arose within the framework of primitive religions, in particular totemism and considered as an important mechanism that regulates social ties in society. In the article, the origin of the concept of taboo, how it influenced religious and moral standards, as well as Western scholars, it is interpreted by such specialists as including J. Fraser, E. Taylor, Z. Freud, and B. Malinovsky is analyzed. At the same time, it is discussed how social discipline and norms are established through taboo, as well as how taboo has gained importance in primitive society.